PENGARUH KOMPENSASI DIREKSI DAN RISIKO PERUSAHAAN PADA AGRESIVITAS PAJAK DI INDONESIA - Reza, Muhammad; Asqolani, Asqolani (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This research aims to examine the effect of directors’ compensation and firm risk on tax aggressiveness and the role of social responsibility disclosure in moderating this influence.Research Methods. Data form manufacturing public companies in Indonesia are used with a purposive sampling method from 2016 to 2019 to obtain 58 samples and 232 observations. This study uses two research models, namely the research model without moderation and the research model with moderation.Research Result and Findings. This research concluded that the compensation for directors and firm risk on tax avoidance has a significant positive effect. In addition to this, corporate social responsibility is also proven to weaken the positive effect of compensation for directors as well as firm risk on tax aggressiveness.